Efzofitimod: a novel anti-inflammatory agent for sarcoidosis - Baughman, Robert P.; Niranjan, Vis; Walker, Gennyne; Burkart, Christoph; Paz, Suzanne; Chong, Yeeting; Siefker, David; Sun, Eileen; Nangle, Leslie; Forster, Sarah; Muders, Michael; Farver, Carol; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Efzofitimod is a first-in-class biologic based on a naturally occurring splice variant of histidyl-tRNA synthetase (HARS) that downregulates immune responses via selective modulation of neuropilin-2 (NRP2). Preclinical data found high expression of NRP2 in sarcoidosis granulomas. Treatment with efzofitimod reduced the granulomatous inflammation induced by P. acnes in an animal model of sarcoidosis. A dose escalating trial of efzofitimod in sarcoidosis with chronic symptomatic pulmonary disease found that treatment with efzofitimod was associated with improved quality of life with a trend towards reduced glucocorticoid use and stable to improved pulmonary function. These studies have led to a large Phase 3 trial of efzofitimod in symptomatic pulmonary sarcoidosis.